2020
DOI: 10.2525/ecb.58.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Duration of Root CHILLING on the Balance between Antioxidant Activity and Oxidative Stress in Spinach

Abstract: It has been proposed that cold stress applied to the root area promotes the production of reactive oxygen species and the increase in antioxidants levels in the plant body. However, changes in the balance between antioxidant activity and oxidative stress in plants under different levels of cold stress remain unexplored. Here, we assessed ascorbic acid content, superoxide dismutase activity, 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, as proxies of antioxidant activity, and malondialdehyde (MDA) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Here, we showed that ascorbic acid increased in seedlings subjected to RZT treatments at 5 and 10°C for 3 days, and declined slightly thereafter. Subsequently, Ito and Shimizu (2020) observed that spinach (Amaranthaceae) exposed to 4°C treatment for 2-7 days exhibited enhanced levels of ascorbic acid. Moreover, Cheminant et al (2011) reported that after 2 weeks of RZT treatment at 5°C, the ascorbic acid content in spinach increased.…”
Section: Treatmentmentioning
confidence: 99%
“…Here, we showed that ascorbic acid increased in seedlings subjected to RZT treatments at 5 and 10°C for 3 days, and declined slightly thereafter. Subsequently, Ito and Shimizu (2020) observed that spinach (Amaranthaceae) exposed to 4°C treatment for 2-7 days exhibited enhanced levels of ascorbic acid. Moreover, Cheminant et al (2011) reported that after 2 weeks of RZT treatment at 5°C, the ascorbic acid content in spinach increased.…”
Section: Treatmentmentioning
confidence: 99%
“…Root temperature plays a critical role in plant growth and influences the concentration of some primary and most secondary metabolites [8][9][10][11]. Reactive oxygen species (ROS) are produced under temperature stress and as an antioxidant defense mechanism, the biosynthesis of bioactive compounds in plants is provoked to counteract the oxidative damage caused by ROS [12].…”
Section: Introductionmentioning
confidence: 99%